"Functional" Inspiratory and Core Muscle Training Enhances Running Performance and Economy. Issue 10 (October 2016) - Tong, Tomas K.; McConnell, Alison K.; Lin, Hua; Nie, Jinlei; Zhang, Haifeng; Wang, Jiayuan
Abstract : Abstract: Tong, TK, McConnell, AK, Lin, H, Nie, J, Zhang, H, and Wang, J. "Functional" inspiratory and core muscle training enhances running performance and economy. J Strength Cond Res 30(10): 2942–2951, 2016—We compared the effects of two 6-week high-intensity interval training interventions. Under the control condition (CON), only interval training was undertaken, whereas under the intervention condition (ICT), interval training sessions were followed immediately by core training, which was combined with simultaneous inspiratory muscle training (IMT)—"functional" IMT. Sixteen recreational runners were allocated to either ICT or CON groups. Before the intervention phase, both groups undertook a 4-week program of "foundation" IMT to control for the known ergogenic effect of IMT (30 inspiratory efforts at 50% maximal static inspiratory pressure [P0 ] per set, 2 sets per day, 6 days per week). The subsequent 6-week interval running training phase consisted of 3–4 sessions per week. In addition, the ICT group undertook 4 inspiratory-loaded core exercises (10 repetitions per set, 2 sets per day, inspiratory load set at 50% post-IMT P0 ) immediately after each interval training session. The CON group received neither core training nor functional IMT. After the intervention phase, global inspiratory and core muscle functions increased in both groups ( p ⩽ 0.05), as evidenced by P0 and a sport-specific endurance plank test (SEPT) performance, respectively. Compared with CON, the ICT group showed larger improvements in SEPT, running economy at the speed of the onset of blood lactate accumulation, and 1-hour running performance (3.04% vs. 1.57%, p ⩽ 0.05). The changes in these variables were interindividually correlated ( r ≥ 0.57, n = 16, p ⩽ 0.05). Such findings suggest that the addition of inspiratory-loaded core conditioning into a high-intensity interval training program augments the influence of the interval program on endurance running performance and that this may be underpinned by an improvement in running economy.